A Comparative Study of Electromagnetic Generator via Finite Element Element Analysis - Dahari, Zuraini; Wong, Chin Chye; Sidek, Othman; Miskam, Muhammad Azman (2011)
Energy scavenging from ambient sources is an attractive alternative to batteries because of an almost unlimited lifetime and is environmentally safe.